(untitled) (Makerere University Journal of Agricultural & Environmental Sciences, 2003)
Two cowpea (Vigna unguiculata L. Walp) varieties, Kanannado and IT97D-941-1 with average seed size of 27.0 g 100’ seeds and 15 g 100’ seeds, respectively, were crossed in the screenhouse. Sufficient backcrosses, F, and F, populations together with the parentals were planted in the field and grown to maturity. Data for 100 seed weight was analysed to determine how this trait can best be improved and also to further understand type of gene effects controlling this trait. Transgressive segregation for large seed was observed in the F, and backcross progeny to the large seeded parent. Large seed was found to be dominant over small seed. Results of the genetic analyses showed the involvement of non-allelic gene interaction in control of this trait. This result further revealed the additive (d) and additive x dominance (j) gene effects as the most important in determining seed size in cowpea. The dominance (h) and dominance x dominance (I) effects were also important but to a lesser extent. Seven gene pairs were estimated to be involved in the control of seed size in cowpea. A narrow sense heritability of 44.2% was estimated for this trait. Genetic advance from F, to F, was estimated as 4.3 g increases in seed size with 5% selection intensity. Selection for transgressive segregates seems to be the best approach for improving seed size in cowpea.